Management Study of the Impact of the Covid-19 Pandemic on Nutrition Vocational Education - Arintina Rahayuni; Yuniarti Yuniarti; Galuh Sintadewi (International Conference on Science, Education, and Technology, 2021)
Vocational education emphasizes the skills aspect. During the pandemic, there was a change in conventional learning models to online, so it was necessary to study the impact on the quality of education (learning outcomes and competency achievement). The design in this study is an explanatory mixed method, differences in learning before and during the pandemic on 143 students, questionnaires were sent using google form. Data analysis using Mann Whitney test. The results showed that there were differences in conditions before and during the pandemic for components 1) lectures (interaction with students) 2) learners (optimism towards challenges) 3) student environment (residence and network access, academic/family support), 4) infrastructure, IT and financing (parental income conditions, monthly expenses and ease of internet access), 5) quality of educational institutions (budget adequacy, popularity of institutions, effectiveness of learning process, 6) learning process (learning access facilities and learning design explanations), 7) learning outcomes (the ability of lecturers to activate students and visualize teaching, continuity of material and motivation), 8) competency achievement (adequacy of knowledge, skills and work experience). Changes in learning methods as a result of the pandemic affect the learning process, so it needs to be followed up so that the quality of education does not decrease.